Database system concepts - Silbenschatz, Abraham; Korth, Henry F. ; Sudarshan, S. (New York, 2020)
Database management has evolved from a specialized computer application to a central component of a modern computing environment, and, as a result, knowl edge about database systems has become an essential part of an education in com-puter science. In this text, we present the fundamental concepts of database manage ment. These concepts include aspects of database design, database languages, and database-system implementation.
Keywords: Database management